The effects of an exercise program for core muscle strengthening in patients with low back pain after cesarean-section: a single blind randomized controlled trial - Iqra Nayyab; Misbah Ghous; Syed Shakil ur Rehman; Irum Yaqoob (Journal of the Pakistan Medical Association, 2021)
Objective: To determine the effects of an exercise programme for core muscle strengthening in patients with low back pain after caesarean section. Method: The single-blind randomised controlled trail was conducted from August 2018 to January 2019 at the Helping Hand for Relief and Development Comprehensive Rehabilitation Centre, Chakwal, Pakistan, and comprised post-caesarean section women aged 25-40 years with low back pain. Patients were randomised into supervised group I and unsupervised group II using the sealed envelope method. Group I received supervised core stability exercise programme, while group II received unsupervised, home-based core stability exercise programme. Baseline and post-intervention values were compared for numeric pain rating scale, Oswestry disability index, inclinometer and core stability assessment. Data was analysed using SPSS 21. Results: Of the 30 subjects, there were 15(50%) in each of the two groups. There was no significant difference at baseline between the groups (p>0.05). Post-intervention results showed significant intra-group and inter-group differences (p<0.05) with respect to all parameters. No improvement was observed for right and left side bending (p>0.05). Conclusion: Supervised core stability exercise programme was more effective in reducing pain and disability, and improved core muscle activation than unsupervised, home-based core exercise programme. Clinical Trial Number: ISRCTN: 12478688 https://doi.org/10.1186/ISRCTN12478688. Key Words: Core stability, C-section, Exercise, Continuous...